Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If i define $f(m,n)=$ $$\sum_{1\leq k\leq mn}\left\{ \frac{k}{m}\right\} \left\{ \frac{k}{n}\right\} .$$

Then prove $$f(m+n,n) - f(m,n) =\frac{n^2-n}{4}$$ for all $m$ and $n$.

This question came from part of answer from this question: A sum of fractional parts.

share|cite|improve this question
up vote 3 down vote accepted

Since $k$ goes from $1$ to $mn$, then the pairs $((k \bmod m),(k \bmod n))$ will meet all cases once.

thus the product is

$$\sum_{1\le k\le m}\left\{\frac{k}{m}\right\}\sum_{1\le t\le n}\left\{\frac{t}{n}\right\}=\frac{m-1}{2}\frac{n-1}{2}\;.$$


share|cite|improve this answer
$\{a\}=a-[a]$, where [a] is the largest integer less than or equal to a. – Yimin May 4 '12 at 3:44

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.